Conductance Changes of Na+ Channels during the Late Na+ Current Flowing under Action Potential Voltage Clamp Conditions in Canine, Rabbit, and Guinea Pig Ventricular Myocytes - Balázs Horváth; Zsigmond M. Kovács; Csaba Dienes; József Óvári; Norbert Szentandrássy; János Magyar; Tamás Bányász; András Varró; Péter P. Nánási (Pharmaceuticals, 2023)
Late sodium current (INa,late) is an important inward current contributing to the plateau phase of the action potential (AP) in the mammalian heart. Although INa,late is considered as a possible target for antiarrhythmic agents, several aspects of this current remained hidden. In this work, the profile of INa,late, together with the respective conductance changes (GNa,late), were studied and compared in rabbit, canine, and guinea pig ventricular myocytes using the action potential voltage clamp (APVC) technique. In canine and rabbit myocytes, the density of INa,late was relatively stable during the plateau and decreased only along terminal repolarization of the AP, while GNa,late decreased monotonically. In contrast, INa,late increased monotonically, while GNa,late remained largely unchanged during the AP in guinea pig. The estimated slow inactivation of Na+ channels was much slower in guinea pig than in canine or rabbit myocytes. The characteristics of canine INa,late and GNa,late were not altered by using command APs recorded from rabbit or guinea pig myocytes, indicating that the different shapes of the current profiles are related to genuine interspecies differences in the gating of INa,late. Both INa,late and GNa,late decreased in canine myocytes when the intracellular Ca2+ concentration was reduced either by the extracellular application of 1 µM nisoldipine or by the intracellular application of BAPTA. Finally, a comparison of the INa,late and GNa,late profiles induced by the toxin of Anemonia sulcata (ATX-II) in canine and guinea pig myocytes revealed profound differences between the two species: in dog, the ATX-II induced INa,late and GNa,late showed kinetics similar to those observed with the native current, while in guinea pig, the ATX-II induced GNa,late increased during the AP. Our results show that there are notable interspecies differences in the gating kinetics of INa,late that cannot be explained by differences in AP morphology. These differences must be considered when interpreting the INa,late results obtained in guinea pig.